Obtaining Carbon Sorbent from “Euromet” LLP Coke Breeze - Muldakhmetov, Z.M.; Ordabaeva, A.T.; Meiramov, M.G.; Gazaliev, A.M.; Shaikenova, Zh.S.; Mukusheva, G.K.; Zhivotova, T.S. (KU Publ., 2022)
The paper presents the results of a physicochemical analysis of a coke sample from “Euromet” LLP (Karaganda, Kazakhstan), which is carbonaceous material with high carbon content, the absence of volatiles matter and low ash content. Carbon sorbents were obtained from low-value fractions of carbonized materials of the Karaganda region coke production by the steam-gas activation. An important advantage of using screenings (coke breeze class 0–10 mm, which was crushed and fractionated to a particle size of 2–5 mm.) is the exclusion of the energy-intensive carbonization stage from the technological process, which releases a large amount of environmentally harmful substances (phenols, cresols, gaseous emissions etc.). The optimal conditions for obtaining a sorbent from low-value coke breeze are a temperature of 850 °C and an activation time of 2 hours. The physicochemical properties (ash content, bulk density, sorption capacity for iodine and methylene blue, total pore volume for water) of carbon sorbents were determined.
«Евромет» ЖШС кокс ұнтағынан көміртекті сорбент алу
Получение углеродного сорбента из коксовой мелочи ТОО «Евромет»
Keywords: coke breeze; coals; sorbents; activation; sorption capacity; ash content; burning; bulk density